2000
DOI: 10.1016/s1010-7940(99)00358-9
|View full text |Cite
|
Sign up to set email alerts
|

Paravalvular leakage after mitral valve replacement: improved long-term survival with aggressive surgery?

Abstract: Following mitral valve replacement, a more aggressive surgical treatment is recommended for patients with paraprosthetic leaks. Surgery should be offered to less symptomatic patients, as well as those not requiring blood transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
151
3
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(163 citation statements)
references
References 11 publications
3
151
3
2
Order By: Relevance
“…The median EuroSCORE II of our cohort (9.5%) falls within the range (7.5% to 9.6%) described by other contemporary series (3,4). Residual mitral PVL has been reported in 2% to 22% of patients following surgical correction (1,3,4). Recurrence of PVL has been cited to occur at a rate of 4% per patient-year (3).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The median EuroSCORE II of our cohort (9.5%) falls within the range (7.5% to 9.6%) described by other contemporary series (3,4). Residual mitral PVL has been reported in 2% to 22% of patients following surgical correction (1,3,4). Recurrence of PVL has been cited to occur at a rate of 4% per patient-year (3).…”
Section: Discussionmentioning
confidence: 99%
“…Hwang and associates (2) reported that 74% of PVLs occur during the first postoperative year. It is extremely rare for PVLs to occur more than 20 years after MVR (1,3,5). The longest interval between the latest MVR and diagnosis of a new PVL in our series was 29 years, which exceeds the longest interval (27 years) reported to date (3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Operative mortality is 6% to 14% (21,22). Besides, PVL can occur approximately in up to 10% of cases of prosthetic valve reoperation (23,24). In most reoperation cases, exposure of the mitral valve is difficult due to severe adhesions.…”
Section: Discussionmentioning
confidence: 99%